Pendapatan Usahatani Bawang Merah (Allium Ascanolicum L.) Di Desa Serubeba Kecamatan Rote Timur Kabupaten Rote Ndao - Huan, Fitra Yublina; Nampa, I Wayan; Elvani, Siska (Undana Press, 2024)
This research was conducted over 1 month from March to April 2024 in Serubeba Village, Rote Timur District, Rote Ndao Regency. The objectives of this research are 1) To determine the income of shallot farming in Serubeba Village, Rote Timur District, Rote Ndao Regency. 2) To determine the feasibility level of shallot farming in Serubeba Village, Rote Timur District, Rote Ndao Regency. The sampling method used in this research is purposive sampling. The sample for this research was taken from 30 farmers who are engaged in shallot farming. The data used are secondary and primary data. The analysis in this research includes income and feasibility analysis using the R/C Ratio analysis method. The results showed that the average production was 1,844.8 kg and the average revenue for shallot farming was IDR 39,146,656/MT. The average total cost incurred was IDR 12,941,520. Thus, it provided an income of IDR 26,846,001/MT. The R/C Ratio of shallot farming for one planting season was 3.18, indicating that shallot farming is feasible (profitable) and increases farming income.